2018
DOI: 10.1002/hyp.13252
|View full text |Cite
|
Sign up to set email alerts
|

Changes in reference evapotranspiration over China during 1960–2012: Attributions and relationships with atmospheric circulation

Abstract: This study investigates reference evapotranspiration (ET0) trends in China from 1960 to 2012 based on the Penman–Monteith equation and gridded meteorological measurements. Under the combined impacts of factors influencing ET0 (i.e., net radiation [RN], mean temperature [TAVE], vapour pressure deficit [VPD], and wind speed [WND]), both seasonal and annual ET0 for the whole China and more than half of the grids decreased over the past 53 years. The attribution analyses suggest that for the whole China, the WND i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 108 publications
1
20
0
1
Order By: Relevance
“…Hence, it is expected that AED is also influenced, but in a complex way due to atmospheric circulation effects on local climate and different sensitivities of AED to each of the governing meteorological variables (Hobbins, Wood, Streubel, & Werner, ; Roderick, Rotstayn, Farquhar, & Hobbins, ; Vicente‐Serrano, Azorin‐Molina, Sanchez‐Lorenzo, Revuelto, López‐Moreno, et al, ; Vicente‐Serrano, Azorin‐Molina, Sanchez‐Lorenzo, Revuelto, Morán‐Tejeda, et al, ; Vicente‐Serrano, Lopez‐Moreno, et al, ). Large‐scale atmospheric circulation patterns influence interannual variability of AED given their control upon local meteorological variables (Chai, Sun, Chen, & Zhou, ; Martens, Waegeman, Dorigo, Verhoest, & Miralles, ).…”
mentioning
confidence: 99%
“…Hence, it is expected that AED is also influenced, but in a complex way due to atmospheric circulation effects on local climate and different sensitivities of AED to each of the governing meteorological variables (Hobbins, Wood, Streubel, & Werner, ; Roderick, Rotstayn, Farquhar, & Hobbins, ; Vicente‐Serrano, Azorin‐Molina, Sanchez‐Lorenzo, Revuelto, López‐Moreno, et al, ; Vicente‐Serrano, Azorin‐Molina, Sanchez‐Lorenzo, Revuelto, Morán‐Tejeda, et al, ; Vicente‐Serrano, Lopez‐Moreno, et al, ). Large‐scale atmospheric circulation patterns influence interannual variability of AED given their control upon local meteorological variables (Chai, Sun, Chen, & Zhou, ; Martens, Waegeman, Dorigo, Verhoest, & Miralles, ).…”
mentioning
confidence: 99%
“…u 2 was the dominant factor contributing to ET 0 in the NMR; this is generally consistent with previous studies in similar regions (Yin et al ., 2009; Han et al ., 2012; Liu and Zhang, 2013; Zhang et al ., 2013; Li et al ., 2014; Fan et al ., 2016; Wang et al ., 2017; Li et al ., 2017c; Chai et al ., 2018; Fan and Thomas, 2018). Table 3 indicates significant positive correlations between ET 0 and u 2 during periods I and II but a weak positive correlation during period III.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been extensive research efforts to investigate the potential impact of climate change on ET 0 in this region. The results suggested that changes in ET 0 for northwest China can primarily be attributed to a decreased wind speed since the 1960s (Yin et al ., 2010; Han et al ., 2012; Huo et al ., 2013; Zhang et al ., 2013; Li et al ., 2014; Fan et al ., 2016; Wang et al ., 2017; Chai et al ., 2018; Fan and Thomas, 2018). Li et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further reduce the possible uncertainties that were introduced by the inhomogeneity of the stations' geographic distribution, we followed Zhang et al [27] and Chai et al [28] to conduct a redistribution algorithm after the screening of the stations. In detail, this process redistributed the station data onto a 0.5 • × 0.5 • equal longitude-latitude grid, and each grid box only contained one station (if any grid contained more than one station, the station data that was last processed would represent the final value of that grid).…”
Section: Observational and Reanalysis Datasetsmentioning
confidence: 99%